The biosorption of cadmium and cobalt and iron ions by yeast Cryptococcus humicola at nitrogen starvation - Kulakovskaya, Tatiana; Ryazanova, Lyubov; Zvonarev, Anton; Khokhlova, Galina; Ostroumov, Vladimir; Vainshtein, Mikhail (Folia microbiologica, 2018)
Yeasts Cryptococcus humicola accumulated cadmium, cobalt, and iron (~ 50, 17, and 4% of the content in the medium, respectively) from the medium containing glucose, phosphate, and 2 mmol/L of metal salts. The effects of metal absorption on the levels of orthophosphate (Pi) and inorganic polyphosphate (polyP) varied for the metals under study. The levels of Pi and polyP increased in the case of cadmium and cobalt, respectively. In the case of iron, no changes in the levels of Pi and polyP were observed. Multiple DAPI-stained polyP inclusions were observed in the cytoplasm of cadmium-containing cells. The intensity of DAPI staining of the cell wall especially increased in case of cobalt and iron accumulation.
Keywords: železo; polyfosfáty; kadmium; Sorption Detoxification; Cadmium; kobalt; Cryptococcus; Biomass; Iron; Nitrogen; sorpční detoxikace; dusík; Cobalt; Polyphosphates; biomasa